Study of pharmacogenomic information in FDA-approved drug labeling to facilitate application of precision medicine. Issue 5 (May 2020) - Mehta, Darshan; Uber, Ryley; Ingle, Taylor; Li, Catherine; Liu, Zhichao; Thakkar, Shraddha; Ning, Baitang; Wu, Leihong; Yang, Junshuang; Harris, Steve; Zhou, Guangxu; Xu, Joshua; et al.
Highlights: FDA-approved drug labeling contains rich pharmacogenomic (PGx) information. FDALabel database features allow navigation of drug labeling information. A total of 261 drugs and 362 drug–biomarker pairs (DBPs) were identified. DBPs can be categorized into Indication, Safety, Dosing and Information. This article facilitates better understanding and utilization of PGx information. Abstract : Pharmacogenomics (PGx), studying the relationship between drug response and genetic makeup of an individual, is accelerating advances in precision medicine. The FDA includes PGx information in the labeling of approved drugs to better inform on their safety and effectiveness. We herein present a summary of PGx information found in 261 prescription drug labeling documents by querying the publicly available FDALabel database. A total of 362 drug–biomarker pairs (DBPs) were identified. We profiled DBPs using frequency of the biomarkers and their therapeutic classes. Four categories of applications (indication, safety, dosing and information) were discussed according to information in labeling. This analysis facilitates better understanding, utilization and translation of PGx information in drug labeling among researchers, healthcare professionals and the public.